Relationship between Maternal Knowledge about Complementary Food and Incidence of Diarrhea in Toddlers Aged 6-8 Months In Calungbungur Village, Pajagan 2023 - Nurhafidoh, Idoh; Yanuarti, Tuty (Prodi DIII Kebidanan La Tansa Mashiro, 2023)
Background: Diarrhea disease is one of the infectious diseases of the digestive tract that is a health problem in the world including Indonesia. Behavioral factors can influence the spread of enteric germs and reduce the risk of diarrhea. Referring to the Pajagan Health Center MTBS register book in 2023, toddlers aged 6-8 months in Ciuyah Village who experienced diarrhea based on gender were 13 boys and 11 girls. Research Objective: To determine the effect of maternal knowledge about complementary feeding (MP-ASI) with the incidence of diarrhea in toddlers aged 6-8 months in Calungbungur Village, Pajagan Health. Center in 2023. Research Methods: This study used quantitative research methods. The research design used a case control design. The total sample was 15 respondents. Case and control samples were taken in an unmatched case control with a ratio of 1: 2. The sampling technique used was simple random sampling. Research Results: The results of the Chi Square Test showed that there was no significant relationship between maternal knowledge about complementary feeding and the incidence of diarrhea in toddlers (p value 1.000). The results of the OR calculation show that mothers with less knowledge about complementary feeding 1.556 times to experience the incidence of diarrhea in toddlers compared to good knowledge (95% CI 0.165-14.654). Conclusion and Suggestion: Health promotion on Clean and Healthy Living Behavior (PHBS) should be carried out regularly so that people in Calungbungur Village understand how to maintain environmental health. Mothers of infants aged 6-8 months should understand the importance of complementary feeding, so as to maintain infant health and reduce the risk of diarrhea.